THE REJECTION OF DIRECT CHIEF EXECUTIVE ELECTION IN HONG KONG UNDER LEUNG CHUN YING ADMINISTRATION - Nabila Wulandari M A Malik (HI 15 UMY 198, 2015)
*198 This research examines the reasons behind the rejection of Hong Kong’s free Chief Executive Election under Leung Chun Ying Administration. As the majority of Hong Kong people have demand to able directly elect the Hong Kong Chief Executive in 2017. This research aims to understand the development of democracy process in Hong Kong. The writer uses the approach of elite concept and theory to analyze the motives of Leung Chun Ying to reject the direct election proposal of the Hong Kong Chief Executive. The writer uses methods of library research which data are secondary source. All data are taken from books, journals, articles on the internet, and other relevant data to the research. Leung Chun Ying’s decision is due to his interests, they are Hong Kong elites to fully control the Hong Kong governmental system, to maintain Hong Kong status quo, and to maintain Hong Kong economic system.